Cricket Shots Analysis Using AI - Khatiwada, Bhuwan; Subedi, Bishwa Prakash; Duwal, Niraj; Gautam, Rewan; Dahal, Suramya Sharma (KEC Journal of Science and Engineering, 2023)
Cricket is often described as a contest between bat and ball, and batting is considered one of its prime disciplines. While batting a batter tries to hit the ball with a different variety of shots to guide the ball in any specific direction of their wish. The types of shots include cover drive, straight drive, pull shot, reverse sweep, and many more. It is tedious task to classify shots manually and provide the insights for the batter. Our goal is to classify the shots using Support Vector Machine (SVM) and to provide an analysis of how well someone plays a particular shot using image processing technique. This can be achieved by collecting the required image data, extracting features, feeding to the machine learning or deep learning algorithms, and generating the classifier output. We have implemented the model using EfficientDet and SVM which works better with less data.